2006
DOI: 10.1177/0739456x06288093
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Equity in HOT Lane Planning

Abstract: This article investigates how concern about equity has arisen in the planning and implementation of high-occupancy/toll lane projects, or so-called “HOT lanes.” Specifically, the research assesses (1) where and how equity issues have surfaced in the debate over HOT lanes and (2) how practicing planners have responded to these equity concerns. By looking explicitly at the planning process through a series of case studies and a review of newspaper coverage, the research suggests strategies for how practitioners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…Specifically, a typical requirement for the wide acceptance of a congestion pricing policy is to be progressive, redistributing welfare from richer to poorer groups of society, normally after taking into account the effect of revenue allocation through compensation, tax reduction or subsidy. On the contrary, a regressive congestion pricing policy, benefiting mainly the richer groups or costing mostly the poorer groups of society, is expected to have a limited acceptability [120,141,206,210,272,300,309,316,324,335,355,362,390]. Recently, [50] used disaggregate data within a simulation framework for different scenario analysis in the Paris region and showed that equity effects can considerably vary with the amount of traffic reduction and the design (toll level and location) of the road pricing scheme.…”
Section: Evaluation and Treatment Of The Impacts Of Road Network Pricingmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, a typical requirement for the wide acceptance of a congestion pricing policy is to be progressive, redistributing welfare from richer to poorer groups of society, normally after taking into account the effect of revenue allocation through compensation, tax reduction or subsidy. On the contrary, a regressive congestion pricing policy, benefiting mainly the richer groups or costing mostly the poorer groups of society, is expected to have a limited acceptability [120,141,206,210,272,300,309,316,324,335,355,362,390]. Recently, [50] used disaggregate data within a simulation framework for different scenario analysis in the Paris region and showed that equity effects can considerably vary with the amount of traffic reduction and the design (toll level and location) of the road pricing scheme.…”
Section: Evaluation and Treatment Of The Impacts Of Road Network Pricingmentioning
confidence: 97%
“…In such schemes, appropriate adjustments of charges, in terms of their level and differences between consecutive charging zones, should be made to avoid the disruptive effects of traffic rerouting to the lower-charge peripheral roads [21]. Other applications of road pricing refer to the (statically or dynamically valued) heavy occupancy toll (HOT) lanes in the United States to allow users of low or single-occupancy vehicles to use a lane if they pay a toll [205,390] and the toll rings in Norway [207,274]. These schemes generally seek to generate revenues and/or recover costs of road building, operations and maintenance, rather than cover congestion and other externality costs, similar to the case of the privately financed toll highways by various concession schemes (see Section 3.4).…”
Section: Practical Applications Of Road Network Pricing Schemesmentioning
confidence: 99%
“…This outcome is seen as particularly inequitable for existing transit users (Lari and Buckeye 1999;Weinstein and Sciara 2006) and appears to be happening along Salt Lake City's I-15, where lane underpricing (due to legal restraints on toll levels) and poor lane enforcement have resulted in new peak-period congestion in the converted HOT lane.…”
Section: Hot Lanes In the United Statesmentioning
confidence: 99%
“…Recently, an NCHRP study regarding the public opinion of congestion pricing projects articulates social equity as a key concern of the public as well as how revenue generated by the project is used (Zmud and Arce 2008). Weinstein and Sciara conclude that social equity has a tendency to shape the overall design of the project, which often includes spending the revenue generated on alternate transportation options for users (Weinstein and Sciara 2006). Thus, it would appear that including transit in the planning and design of congestion pricing projects appears to be essential to make it politically tenable.…”
Section: Introductionmentioning
confidence: 99%